Elections of Deputies of the State Duma of the Second Convocation (1995-1999): the Success of the Anti-reform Opposition, the Failure of the “Party of Power” and the Defeat of the Democrats (to the 30th Anniversary of the Russian Federation) - Yu. A. Nisnevich (Проблемы постсоветского пространства, 2021)
The article is devoted to the political and historical analysis of the elections of deputies of the State Duma of the second convocation in 1995. The political context of these elections is assessed as a confrontation between the “party in power” and the anti-reform opposition. To counteract the opposition, the “party in power” created its own political structure to participate in the elections — the movement “Our Home-Russia” (NDR), headed by Prime Minister Viktor Chernomyrdin. An analysis of the process of creating the PDR movement, which took place under the auspices of the Presidential Administration, confirms the use of the administrative resource of the presidential and executive powers in this process. The creation of the NDR movement led to the erosion of the reformist-democratic wing. The weakening of this flank was also facilitated by the fact that the political organizations forming it could not unite. Two leading political organizations with a reformist-democratic orientation — Yegor Gaidar’s Democratic Choice of Russia party and Grigory Yavlinsky’s Yabloko public association did not create a common electoral bloc, although there were objective prerequisites for this. A significant aspect of the 1995 election campaign was the fact that Russian industry corporations and financial and industrial groups began to show an active interest in the elections of deputies. They began to incorporate lobbyists of their interests into the parliamentary corps. At the elections of deputies of the State Duma of the second convocation in 1995. success accompanied the anti-reform opposition and, above all, the Communist Party of the Russian Federation, failure befell the “party of power” represented by the NDR movement, and the reformist democrats who failed to unite suffered a crushing defeat. The State Duma of the second convocation had a pronounced anti-reform and oppositional character to the incumbent president and the executive branch, but at the same time it was a fairly independent political institution, which retained certain opportunities for competitive legislative activity and the search for compromises in crisis situations. The 1995 elections cannot be assessed as completely fair and free, and, starting with these elections, the bacillus of electoral corruption was introduced into the organism of Russian politics.